Laminate, and lid material and packaging body using the same
By adjusting the amount of the anchor coating and using the anchor layer and heat sealing layer of a specific resin combination, the problem of insufficient heat sealing strength in the low temperature is solved, and efficient heat sealing of the container at low temperature is achieved, reducing energy consumption and damage.
Patent Information
- Application Number
- JP2023114106
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-11
- Publication Date
- 2025-01-24
AI Technical Summary
The prior art is difficult to achieve sufficient heat seal strength during low-temperature heat sealing, resulting in damage to containers and contents during heating and increasing energy consumption.
By adjusting the amount of the anchor coating and using an anchor layer and a heat sealing layer containing a combination of polyester resin and a specific resin, it is ensured that good heat sealing strength can be maintained at low temperatures, the anchoring layer does not cure with isocyanate, and the heat sealing layer contains acrylic resin and vinyl chloride acetate copolymer resin.
Excellent heat sealing strength under low temperature heat sealing conditions is achieved, reducing damage to containers and contents, and reducing energy consumption.
Smart Images

Figure 2025011784000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminate, and a lid material and a packaging material using the same. [Background technology]
[0002] Packaging containers for yogurt, etc., consist of a lid material such as polyethylene terephthalate (PET) film and a container such as polystyrene. The container and lid material are thermally bonded together using a heat sealant, but in order to achieve sufficient adhesion to both the PET film and the PS container, the container is made up of a two-layer structure in which an anchor coat layer is placed on the PET film and a heat seal layer is placed on top of that.
[0003] So far, a laminate formed by sequentially laminating an anchor coat layer and a heat seal layer on one side of a base film made of a PET film, and a covering material using the same have been reported (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 5580067 Summary of the Invention [Problem to be solved by the invention]
[0005] When using the lid material of Patent Document 1, the heating temperature during heat sealing is usually about 200° C. In order to reduce damage to the container and contents during heating and from the standpoint of energy saving, there is a demand for materials that can be heat sealed at lower temperatures. However, since lowering the heating temperature reduces the heat seal strength, it has been difficult to achieve sufficient heat seal strength at a lower temperature.
[0006] The present embodiment aims to solve the above-mentioned conventional problems and achieve the following objectives: That is, the present embodiment aims to provide a laminate that has excellent heat seal strength even in low-temperature heat treatment by adjusting the application amount of an anchor coating agent, and a lid material and a package using the same. [Means for solving the problem]
[0007] The present embodiment is based on the findings of the present inventors, and the means for solving the above problems are as follows. [1] A film having a base film, an anchor coat layer provided on one side of the base film, and a heat seal layer provided on the anchor coat layer, The anchor coat layer had a coating weight of 1.0 g / m after drying. 2 Super 6g / m 2 A laminate characterized in that: [2] The laminate according to [1], wherein the anchor coat layer contains a polyester resin. [3] The laminate according to [1] or [2], wherein the anchor coat layer is not isocyanate-cured. [4] The laminate according to any one of [1] to [3], wherein the anchor coat layer does not contain an acrylic resin. [5] The laminate according to any one of [1] to [4], wherein the heat seal layer contains at least an acrylic resin and / or a vinyl chloride-vinyl acetate copolymer resin. [6] The laminate according to [5], wherein the heat seal layer further contains an epoxy resin. [7] The heat seal layer has a coating weight of 1 g / m after drying. 2 More than 6g / m 2 The laminate according to any one of the following items [1] to [6]: [8] The ratio of the coating weight of the anchor coat layer to the dry coating weight of the heat seal layer is The laminate according to any one of [1] to [7], wherein the coating weight of the anchor coat layer / the coating weight of the heat seal layer=0.1 or more. [9] The laminate according to any one of [1] to [8], wherein the surface of the base film in contact with the anchor coat layer is a film constituted by a polyester layer.
[10] The laminate according to any one of [1] to [9], which is used as a lid material.
[11] A container having the laminate according to
[10] as a lid material and a recess, The packaging body, wherein the lid material is heat-sealable to the opening of the container. Effect of the Invention
[0008] According to this embodiment, by adjusting the application amount of the anchor coating agent, it is possible to provide a laminate having excellent heat seal strength even when subjected to low-temperature heat treatment, and a covering material and a packaging material using the same. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of the laminate of the present embodiment. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing a precursor sheet for the laminate of the present embodiment. [Diagram 3] FIG. 3 is a schematic cross-sectional view showing an example of a packaging body provided with the lid member of this embodiment. [Figure 4] FIG. 4 is a diagram showing the evaluation results of the seal strength of Examples 1 to 4 and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] (Laminate) A laminate according to one embodiment of the present invention (sometimes referred to as a laminate according to the present embodiment) comprises a base film, an anchor coat layer provided on one side of the base film, and a heat seal layer provided on the anchor coat layer. The anchor coat layer has a coating amount of 1 g / m2 after drying. 2 Super 6g / m 2 The present invention is characterized in that: The surface of the base film that comes into contact with the anchor coat layer is preferably a film that is made of a polyester layer.
[0011] 1, the laminate of this embodiment is, for example, a laminate 10 having at least an anchor coat layer 2 provided directly on a base film 1 and a heat seal layer 3 provided on the anchor coat layer, laminated in the order of base film 1 / anchor coat layer 2 / heat seal layer 3. It is preferable that the surface of the base film 1 that contacts the anchor coat layer is composed of a polyester layer. The heat seal layer 3 is the inside of the packaging body 100 shown in Fig. 3 and forms a heat seal surface with the container 30 described below. The heat seal layer 3 of the laminate enables the packaging body 100 to be thermally bonded to the opening of the container 30. The laminate can be suitably used as a lid material for the packaging material of the present invention.
[0012] [Base film] The substrate film used in the laminate of the present embodiment is preferably a film whose surface in contact with the anchor coat layer is constituted by a polyester layer.
[0013] <Polyester layer> The polyester layer contains a polyester resin as a main component and may further contain other components as necessary, but is preferably made of a polyester resin. The content of the polyester resin is 50% by mass or more, preferably 70% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, and particularly preferably 95% by mass or more, based on the total amount of the polyester layer. The polyester layer is preferably a polyethylene terephthalate film.
[0014] "First polyester resin" The polyester resin (sometimes referred to as the polyester resin of the base film or simply as the first polyester resin) which is a component of the polyester layer of the base film according to the present embodiment is not particularly limited and can be appropriately selected according to the purpose, and examples thereof include polyethylene terephthalate, polyethylene naphthalate, polyethylene isophthalate, polybutylene terephthalate, etc. Among these, polyethylene terephthalate is preferred.
[0015] Examples of the substrate film according to this embodiment include films made of PET (polyethylene terephthalate), A-PET (amorphous polyethylene terephthalate), PBT (polybutylene terephthalate), and the like.
[0016] The average thickness of the base film is not particularly limited and can be appropriately selected depending on the purpose, but is preferably from 10 μm to 30 μm, and more preferably from 12 μm to 25 μm.
[0017] [Anchor coat layer] The anchor coat layer of the laminate of this embodiment preferably contains a polyester resin. The anchor coat layer may or may not be isocyanate cured. In order to further improve low-temperature heat sealability, it is preferable that the anchor coat layer is not isocyanate cured. The anchor coat layer that is not isocyanate cured is in a state in which the thermoplastic resin used in the anchor coat layer is solidified, and is softer than the anchor coat layer cured with a curing agent such as polyisocyanate, so it is thought that it can contribute to improving the low-temperature heat sealability of the heat seal layer provided on the anchor coat layer. The anchor coat layer may contain other resins such as acrylic resins in addition to the polyester resin. It is preferable that the anchor coat layer does not contain an acrylic resin. Incidentally, "the anchor coat layer is not isocyanate-cured" means that curing is not carried out by adding polyisocyanate as a curing agent. "The anchor coat layer does not contain an acrylic resin" means that it does not substantially contain an acrylic resin. In other words, it means that the anchor coat layer does not contain an acrylic resin, or, even if it contains unavoidable impurities or the like, the anchor coat layer may contain 0% by mass to 0.5% by mass of the acrylic resin relative to the anchor coat layer.
[0018] <Second polyester resin> The polyester resin (sometimes referred to as the polyester resin of the anchor coat layer, or simply as the second polyester resin) which is a component of the anchor coat layer according to the present embodiment is not particularly limited and can be appropriately selected according to the purpose, and examples thereof include polyethylene terephthalate, polyethylene naphthalate, polyethylene isophthalate, polybutylene terephthalate, etc. These may be used alone or in combination of two or more kinds. The second polyester resin may be the same as or different from the first polyester resin. The second polyester resin is preferably different from the first polyester resin. For example, the second polyester resin preferably has a lower Tg than the first polyester resin.
[0019] The second polyester resin, which is a constituent component of the anchor coat layer according to this embodiment, may contain polyester polyol, polyether ester polyol, polyester amide polyol, polyester urethane polyol, or a mixture thereof.
[0020] Examples of the polyester polyols include polyester polyols obtained by reacting dibasic acids such as terephthalic acid, isophthalic acid, adipic acid, azelaic acid, and sebacic acid, or dialkyl esters thereof, or mixtures thereof, with glycols such as ethylene glycol, propylene glycol, diethylene glycol, butylene glycol, neopentyl glycol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, 3,3'-dimethylolheptane, polyoxyethylene glycol, polyoxypropylene glycol, and polytetramethylene ether glycol, or mixtures thereof; and polyester polyols obtained by ring-opening polymerization of lactones such as polycaprolactone, polyvalerolactone, and poly(β-methyl-γ-valerolactone).
[0021] Examples of polyether ester polyols include polyether ester polyols obtained by reacting a dibasic acid such as terephthalic acid, isophthalic acid, adipic acid, azelaic acid, sebacic acid, or the like, or a dialkyl ester thereof, or a mixture thereof, with a polyether polyol obtained by polymerizing an oxirane compound such as ethylene oxide, propylene oxide, butylene oxide, tetrahydrofuran, or the like, using a low molecular weight polyol such as water, ethylene glycol, propylene glycol, trimethylolpropane, glycerin, or the like as an initiator.
[0022] The polyesteramide polyol can be obtained by using, in the above esterification reaction, an aliphatic diamine having an amino group, such as ethylenediamine, propylenediamine, or hexamethylenediamine, as a raw material.
[0023] The polyester urethane polyol is a polyol having a urethane bond in one molecule, and is obtained, for example, by reacting a polyester polyol or polyether ester polyol having a number average molecular weight of 200 to 20,000 with an organic polyisocyanate at an NCO / OH ratio of less than 1, preferably 0.9 or less. The organic polyisocyanate is not particularly limited, and for example, the one described below can be used.
[0024] The second polyester resin preferably has, for example, a lower Tg than the first polyester resin that is a constituent of the base film. A method for obtaining a polyester resin with a lower Tg can be, for example, a method for producing a polyester resin by adjusting the raw materials, catalyst, and reaction conditions used according to a known method for producing a polyester resin.
[0025] From the viewpoint of further improving the heat seal strength at low temperatures, the second polyester resin, which is a constituent component of the anchor coat layer of the laminate of this embodiment, preferably has a Tg of, for example, 60° C. or less, more preferably 50° C. or less, and even more preferably 40° C. or less. From the viewpoint of blocking properties, the Tg is preferably 0° C. or more, more preferably 5° C. or more, and even more preferably 10° C. or more.
[0026] The anchor coat layer of the laminate of the present embodiment may further contain other known additives in addition to the polyester resin. The other additives are not particularly limited and can be appropriately selected depending on the purpose. Examples of the additives include inorganic fine particles, lubricants, waxes, fillers, viscosity modifiers, preservatives, antibacterial agents, rust inhibitors, antioxidants, crosslinking agents, curing agents, curing catalysts, light stabilizers, ultraviolet absorbers, photocatalytic compounds, dyes, inorganic pigments, organic pigments, extender pigments, plasticizers, and antistatic agents. Among these, it is preferable to contain an anti-blocking agent such as wax in order to prevent blocking.
[0027] "Inorganic fine particles" The inorganic fine particles are not particularly limited and may be appropriately selected depending on the purpose, but silica is preferred. Among these, synthetic amorphous silica is preferred because it is easy to obtain a desired particle size. The shape of the silica is not particularly limited and can be appropriately selected depending on the purpose, and may be, for example, spherical silica consisting of a single particle, or amorphous silica in which secondary particles or tertiary particles are formed from a plurality of primary particles. Among these, spherical silica is preferred in that it can improve the blocking property of the heat seal layer, and amorphous silica is preferred in that it can improve the heat seal strength. These may be used alone or in combination of two or more kinds.
[0028] Examples of spherical silica include Admafine SO-C4, SO-C5, and SO-E4 manufactured by Admatechs Co., Ltd.; UFP-30 and SFP-30M manufactured by Denka Co., Ltd.; Seahoster KE series manufactured by Nippon Shokubai Co., Ltd.; and SYLOSPHERE series and Sylysia series manufactured by Fuji Silysia Chemical Ltd. The average particle size of the spherical silica is preferably 0.1 μm or more, more preferably 0.5 μm or more, and even more preferably 1.0 μm or more. As an example of amorphous silica, there is AEROSIL manufactured by EVONIK. TM 200, R972; HDK H15, H18 manufactured by Asahi Kasei Wacker Silicone Co., Ltd.; MT-10, DM-20S manufactured by Tokuyama Corporation. The average particle size of the amorphous silica is preferably 50 nm or less, more preferably 30 nm or less, and even more preferably 20 nm or less.
[0029] The content of the inorganic fine particles is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 0.1% by mass to 10% by mass, and more preferably 0.1% by mass to 3% by mass, relative to 100 parts by mass of the resin of the heat seal layer. If the content is from 0.1% by mass to 10% by mass, it is favorable in terms of improving the blocking property and the heat seal strength.
[0030] "Lubricant" Examples of lubricants include fatty acid amide waxes such as oleic acid amide, erucic acid amide, stearic acid amide, behenic acid amide, ethylene bis oleic acid amide, and ethylene bis erucic acid amide; animal and vegetable oil waxes such as rice wax, carnauba wax, candelilla wax, lanolin wax, beeswax, whale oil, and beef tallow; petroleum waxes such as petroleum jelly, paraffin wax, microcrystalline wax, polyethylene wax, polypropylene wax, PTFE wax, and linear higher alcohols; silicones such as dimethylpolysiloxane and modified silicones in which at least one methyl group in the side chain of dimethylpolysiloxane is substituted with an organic group other than a methyl group (such as a carbinol group, a polyether group, or an alkyl group having 2 or more carbon atoms); fatty acids such as stearic acid, behenic acid, 12-hydroxystearic acid, and stearyl alcohol; and higher alcohols.
[0031] The content of the polyester resin in the anchor coat layer is not particularly limited and can be appropriately selected depending on the purpose, but for example, it is preferably 80% by mass or more, more preferably 90% or more, and even more preferably 95% or more.
[0032] The anchor coat layer is applied in an amount of 1 g / m after drying in order to further improve the heat seal strength at low temperatures. 2 and 1.2 g / m 2 It is preferable that the content is 1.5 g / m or more. 2 More preferably, it is 2.5 g / m or more. 2 More preferably, it is 6 g / m or more. 2 It is preferable that the thickness is less than 5 g / m 2 More preferably, it is 4 g / m or less. 2 It is even more preferable that: Anchor coat layer: 1g / m 2By increasing the coating amount compared to conventional methods so that the low-temperature heat sealability exceeds 100%, it is possible to improve the low-temperature heat sealability. This is thought to be because the resin components in the anchor coat layer soften and melt, allowing the heat seal function to be expressed.
[0033] The anchor coat layer can be formed, for example, by directly applying an anchor coat agent, in which the polyester resin or the like is dispersed or dissolved in a solvent, to the base film and drying the same. In addition, when the base film includes a polyester layer, the anchor coat layer can be formed by directly coating the polyester layer of the base film and drying the polyester layer. The region where the anchor coat layer is to be provided may be on the polyester layer of the base film, and the anchor coat layer can be applied to the entire surface or part of the polyester layer.
[0034] As the anchor coating agent, a heat sealing agent according to the present embodiment described below can be suitably used. The method for applying the anchor coating agent is not particularly limited and can be appropriately selected depending on the purpose, and for example, a roll coater, gravure coater, flexo coater, air doctor coater, blade coater, air knife coater, squeeze coater, impregnation coater, transfer roll coater, kiss coater, curtain coater, cast coater, spray coater, die coater, offset printing machine, screen printing machine, etc. After coating, a drying step in an oven or the like can be used.
[0035] The drying method is not particularly limited, and may be appropriately selected from conventionally known means such as hot air, electric heat, infrared rays, electron beams, etc. The heating temperature in drying is preferably 50° C. to 250° C., and the heating time is preferably 0.1 seconds to 30 seconds.
[0036] <Anchor coating agent> The anchor coating agent according to this embodiment contains the second polyester resin described above, and preferably further contains other components such as a solvent and other additives as necessary. The second polyester resin and the anchor coating agent in the anchor coating agent of this embodiment can be appropriately selected from the items explained in the laminate of this embodiment above.
[0037] The amount of components (solid content) other than the solvent in the anchor coating agent is preferably 20% by mass to 70% by mass.
[0038] The solvent is not particularly limited and can be appropriately selected depending on the purpose. Examples of the solvent include aromatic hydrocarbon organic solvents such as toluene, xylene, Solvesso #100, Solvesso #150, etc.; aliphatic hydrocarbon organic solvents such as hexane, heptane, octane, decane, etc.; ester organic solvents such as methyl acetate, ethyl acetate, isopropyl acetate, butyl acetate, amyl acetate, ethyl formate, butyl propionate, etc.; and water-miscible organic solvents. Examples of the water-miscible organic solvent include alcohol-based organic solvents such as methanol, ethanol, propanol, and butanol; ketone-based organic solvents such as acetone, methyl ethyl ketone, and cyclohexanone; and glycol ether-based organic solvents such as ethylene glycol (mono, di)methyl ether, ethylene glycol (mono, di)ethyl ether, ethylene glycol monopropyl ether, ethylene glycol monoisopropyl ether, monobutyl ether, diethylene glycol (mono, di)methyl ether, diethylene glycol (mono, di)ethyl ether, diethylene glycol monoisopropyl ether, diethylene glycol monobutyl ether, triethylene glycol (mono, di)methyl ether, propylene glycol (mono, di)methyl ether, propylene glycol monopropyl ether, propylene glycol monobutyl ether, and dipropylene glycol (mono, di)methyl ether. Among these, ester-based organic solvents, ketone-based organic solvents such as methyl ethyl ketone, and mixtures thereof are preferred. In recent years, from the viewpoint of the working environment, it is more preferable not to use aromatic solvents such as toluene and xylene.
[0039] The additives are not particularly limited and can be appropriately selected depending on the purpose. Examples of the additives include wax, filler, viscosity modifier, preservative, antibacterial agent, rust inhibitor, antioxidant, crosslinking agent, curing agent, curing catalyst, light stabilizer, ultraviolet absorber, photocatalytic compound, dye, inorganic pigment, organic pigment, extender pigment, plasticizer, and antistatic agent. Among these, it is preferable to contain an anti-blocking agent such as wax in order to prevent blocking.
[0040] [Heat seal layer] The heat seal layer used in the laminate of this embodiment may be made of a known resin, such as at least one selected from styrene-butadiene copolymer resin, (meth)acrylate-styrene copolymer resin, (meth)acrylate resin, vinyl chloride vinyl acetate copolymer resin, olefin-α,β unsaturated carboxylic acid copolymer resin, polyolefin resin, or polyester resin. The heat seal layer used in the laminate of this embodiment preferably contains at least one selected from, for example, (meth)acrylate resin, vinyl chloride vinyl acetate copolymer resin. The heat seal layer may further contain an epoxy resin.
[0041] <(Meth)acrylate Resin> The (meth)acrylate resin is not particularly limited as long as it is a homopolymer or copolymer of (meth)acrylate, and examples of the copolymer include copolymers obtained by copolymerizing (meth)acrylate with a vinyl monomer copolymerizable therewith. When using an aqueous solvent, it is preferable that the copolymer has an acid value in order to impart water dispersibility or water solubility. The (meth)acrylate used as a constituent component of the (meth)acrylate homopolymer or copolymer is not particularly limited, and examples thereof include (meth)acrylates such as acrylic acid, methacrylic acid, methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and dodecyl (meth)acrylate, as well as (meth)acrylic acid derivatives having a functional group such as hydroxyethyl (meth)acrylate, hydroxybutyl (meth)acrylate, (meth)acrylic acid amide, (meth)acrylonitrile, and α-methyl (meth)acrylonitrile. Examples of (meth)acrylates and vinyl monomers copolymerizable with (meth)acrylates include aromatic (meth)acrylates such as benzyl (meth)acrylate; hydroxyl group-containing monomers such as 2-hydroxyethyl (meth)acrylate and 2-hydroxypropyl (meth)acrylate; alkyl polyalkylene glycol mono(meth)acrylates such as methoxypolyethylene glycol mono(meth)acrylate and methoxypolypropylene glycol mono(meth)acrylate; fluorine-based (meth)acrylates such as perfluoroalkylethyl (meth)acrylate; aromatic vinyl compounds such as styrene, styrene derivatives (p-dimethylsilylstyrene, (p-vinylphenyl)methylsulfide, p-hexynylstyrene, p-methoxystyrene, p-tert-butyldimethylsiloxystyrene, o-methylstyrene, p-methylstyrene, p-tert-butylstyrene, α-methylstyrene, etc.), vinylnaphthalene, vinylanthracene, and 1,1-diphenylethylene; glycidyl (meth)acrylate, epoxy (meth)acrylate, ethylene glycol di(meth)acrylate, etc. ) acrylate, diethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, tetramethylene glycol tetra(meth)acrylate, 2-hydroxy-1,3-diacryloxypropane, 2,2-bis[4-(acryloxymethoxy)phenyl]propane, 2,2-bis[4-(acryloxyethoxy)phenyl]propane, dicyclopentenyl(meth)acrylate tricyclodecanyl(meth)acrylate, tris(acryloxyethyl)isocyanurate, urethane(meth)acrylate, etc. (meth)acrylate compounds having an alkylamino group, such as dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, and dimethylaminopropyl (meth)acrylate; vinylpyridine compounds, such as 2-vinylpyridine, 4-vinylpyridine, and naphthylvinylpyridine; and conjugated dienes, such as 1,3-butadiene, 2-methyl-1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, 1,3-hexadiene, and 1,3-cyclohexadiene.These monomers can be used alone or in combination of two or more.
[0042] <Vinyl chloride vinyl acetate copolymer resin> The vinyl chloride / vinyl acetate copolymer resin is not particularly limited as long as it is a copolymer of vinyl chloride and vinyl acetate. From the viewpoint of improving heat sealability, it is preferable that the vinyl chloride / vinyl acetate copolymer contains an acid group, and more preferable that the vinyl chloride / vinyl acetate copolymer resin is acid-modified. As the acid group, it is preferable that maleic acid or fumaric acid is used.
[0043] <Epoxy resin> The epoxy resin is not particularly limited and may be a conventionally known one, and examples thereof include bisphenol type epoxy resins such as bisphenol A type epoxy resins and bisphenol F type epoxy resins; biphenyl type epoxy resins such as biphenyl type epoxy resins and tetramethylbiphenyl type epoxy resins; and dicyclopentadiene-phenol addition reaction type epoxy resins. These may be used alone or in combination of two or more. Among these, it is preferable to use bisphenol type epoxy resins because of their high adhesiveness to various substrates.
[0044] <Styrene-butadiene copolymer resin> Examples of styrene-butadiene copolymer resins include styrene-butadiene-styrene block copolymers, styrene-isoprene-styrene block copolymers, styrene-isobutylene-styrene block copolymers, styrene-ethylenebutylene-styrene block copolymers which are hydrogenated styrene-butadiene-styrene block copolymers, and styrene-ethylenepropylene-styrene block copolymers which are hydrogenated styrene-isoprene-styrene block copolymers. In addition, instead of the styrene constituting these block copolymers, block copolymers composed of styrene derivatives such as α-methylstyrene, 3-methylstyrene, 4-propylstyrene, and 4-cyclohexylstyrene can also be used. Furthermore, those to which an organic acid group such as itaconic acid or maleic anhydride has been added to these styrene-butadiene copolymer resins can also be used. Among these, styrene-ethylenebutylene-styrene block copolymers, maleic acid-modified styrene-ethylenebutylene-styrene block copolymers, and the like are preferred.
[0045] <(Meth)acrylate-styrene copolymer resin> The (meth)acrylate-styrene copolymer resin is a copolymer of (meth)acrylate and styrene. The (meth)acrylate-styrene copolymer may be a copolymer of (meth)acrylate, styrene, and, if necessary, other monomers.
[0046] The (meth)acrylate is not particularly limited, and any known (meth)acrylic acid ester can be appropriately selected depending on the purpose. Examples thereof include alkyl esters, hydroxyalkyl esters, and alkoxyalkyl esters of acrylic acid or methacrylic acid. Examples of the (meth)acrylate include acrylic acid esters such as methyl acrylate, ethyl acrylate, isopropyl acrylate, n-propyl acrylate, n-butyl acrylate, isobutyl acrylate, 2-ethylhexyl acrylate, isooctyl acrylate, n-octyl acrylate, 2-hydroxyethyl acrylate, and 2-methoxyethyl acrylate; and methacrylic acid esters such as methyl methacrylate, ethyl methacrylate, isopropyl methacrylate, n-propyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, n-hexyl methacrylate, 2-ethylhexyl methacrylate, n-lauryl methacrylate, 2-hydroxyethyl methacrylate, and 2-ethoxyethyl methacrylate. These can be used alone or in combination of two or more. Among these, n-butyl methacrylate and methyl methacrylate are preferred.
[0047] The heat seal layer can be formed, for example, by directly applying a heat sealant, which is prepared by dispersing or dissolving the resin or the like in a solvent, onto the anchor coat layer of the base film and drying the applied heat seal layer. The region where the heat seal layer is provided may be on the anchor coat layer of the base film, and the heat seal layer can be applied to the entire surface or part of the polyester layer.
[0048] As the heat-sealing agent, a heat-sealing agent according to the present embodiment described below can be suitably used. The method for applying the heat sealing agent is not particularly limited and can be appropriately selected depending on the purpose, and for example, a roll coater, a gravure coater, a flexo coater, an air doctor coater, a blade coater, an air knife coater, a squeeze coater, an impregnation coater, a transfer roll coater, a kiss coater, a curtain coater, a cast coater, a spray coater, a die coater, an offset printing machine, a screen printing machine, etc. After application, a drying step may be performed in an oven, etc.
[0049] The drying method is not particularly limited, and may be appropriately selected from conventionally known means such as hot air, electric heat, infrared rays, electron beams, etc. The heating temperature in drying is preferably 50° C. to 250° C., and the heating time is preferably 0.1 seconds to 30 seconds.
[0050] The amount of the heat sealant applied is not particularly limited and can be appropriately selected depending on the desired seal strength and the substrate film. 2 ~6.0g / m 2 is preferred.
[0051] "Heat sealant" The heat sealant of the present invention is a heat sealant that is applied directly onto the anchor coat layer, and contains each of the resin components contained in the heat seal layer, and further contains other components such as solvents and additives as necessary. Each resin component in the heat-sealing agent of the present invention can be appropriately selected from those described above for the heat-sealing layer of the present invention. The heat-sealing agent preferably contains an acrylic resin and / or a vinyl chloride-vinyl acetate copolymer resin, and more preferably further contains an epoxy resin.
[0052] The total content (or solids concentration) of each resin component other than the solvent is preferably 20% by mass to 70% by mass.
[0053] The solvent is not particularly limited and can be appropriately selected depending on the purpose. For example, the solvents used in anchor coating agents can be used.
[0054] The additives are not particularly limited and can be appropriately selected depending on the purpose. Examples of the additives include wax, filler, viscosity modifier, preservative, antibacterial agent, rust inhibitor, antioxidant, crosslinking agent, curing agent, curing catalyst, light stabilizer, ultraviolet absorber, photocatalytic compound, dye, inorganic pigment, organic pigment, extender pigment, plasticizer, and antistatic agent. Among these, it is preferable to contain an anti-blocking agent such as wax in order to prevent blocking. In the laminate of the present invention, the ratio of the coating weight of the anchor coat layer to the dry coating weight of the heat seal layer (anchor coat layer coating weight / heat seal layer coating weight) is preferably 0.1 or more, more preferably 0.3 or more, more preferably 0.5 or more, more preferably 1.0 or more, and more preferably 1.5 or more. When the coating weight ratio of the anchor coat layer is large, the heat seal strength in the low temperature range tends to be high. On the other hand, from the viewpoint of maintaining the heat sealability, the coating weight of the anchor coat layer / the coating weight of the heat seal layer is preferably 5 or less, and more preferably 2.5 or less.
[0055] <Other layers> The laminate may further include other layers such as a deposition layer, a barrier layer, a printed layer, etc. The other layers are provided on the surface of the base film opposite to the surface on which the heat seal layer is provided. The laminate preferably has a vapor deposition layer, which can impart gas barrier properties. The laminate preferably has a barrier layer, for example, when the contents are food and drink, in that it can protect the contents from water vapor and / or oxygen and ensure high storage stability. The other layer may also be a print layer on which printing of the packaging film can be provided. The laminate may further have the other layer on the side of the base film opposite to the side on which the heat seal layer is provided, and may be a laminate laminated in the order of other layer / base film / anchor coat layer / heat seal layer.
[0056] (lid material) The laminate of the present embodiment can be used, for example, as a lid material for use in a package described below.
[0057] (packaging) A package according to one embodiment of the present invention (sometimes referred to as the package according to the present embodiment) includes a lid material and a container (base material) having a recess, and the lid material is the laminate according to the present embodiment. The lid material can be thermally bonded to the opening of the container. The material of the container is preferably polystyrene resin.
[0058] The packaging body has a container (base material) with a recess and a lid material, and after the item to be contained (also called the contents) is placed in the recess, the lid material is placed over it, and the air is removed or replaced with an inert gas or the like, and the contact portion between the container and the lid material is heat-sealed. The shape of the recess in the packaging body and the seal width or area between the lid material and the container vary depending on the shape and form of the contents to be packaged and cannot be uniquely specified, but are not particularly limited and can be selected as appropriate depending on the intended application form.
[0059] The use of the packaging material is not particularly limited and can be appropriately selected depending on the purpose, but it is preferably for packaging food and drink. The food and drink products are not particularly limited and can be appropriately selected depending on the purpose. Examples of the food and drink products include foods such as yogurt, pudding, jelly, retort foods, instant foods, and prepared foods; and general beverages such as fermented lactic acid bacteria drinks, water, tea, coffee soft drinks, milk, soy milk, and soup.
[0060] 3 is a schematic cross-sectional view showing an example of the package of the present invention. The package 100 is a package having a lid 20 and a container 30 having a recess, and contents 40 (e.g., yogurt, etc.) can be accommodated in the recess. The lid 20 can be thermally bonded to the opening of the container 30. Here, the lid material 20 is the laminate of this embodiment (for example, the laminate 10 shown in FIG. 1), and the heat seal layer 3 of the laminate 10 is heat-adherable to the opening of the container 30 and is heat-sealed.
[0061] [container] The container (base material) is not particularly limited and may be any known container having a recess and an opening depending on the purpose, but a container molded from a resin is preferred. The material of the resin is not particularly limited and can be appropriately selected depending on the purpose, but polystyrene resin is preferable.
[0062] There are no particular limitations on the method for manufacturing a container having a recess, and any known method can be selected depending on the purpose. For example, there is a method of molding a container having a recess capable of accommodating an object from a sheet-like film using a mold having a specific shape (e.g., a shape corresponding to the object to be contained). EXAMPLES
[0063] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples. (raw materials, etc.) Second polyester resin (polyester resin as a component of the anchor coat layer) 1: Polyester resin with Tg of 22°C Second polyester resin (polyester resin as a constituent of the anchor coat layer) 2: polyester resin with Tg of 4°C Lubricant: Hydroxystearyl alcohol MEK: Methyl ethyl ketone Ethyl acetate: Silica gel: Silica 446D, manufactured by Fuji Silysia Chemical Co., Ltd. Hardener: Isocyanate-based hardener (DIC Graphics Corporation, KX-75) Heat seal layer Acrylic resin: A commercially available acrylic resin whose main component is n-butyl methacrylate. Vinyl chloride resin: Solvine M5, manufactured by Nissin Chemical Industry Co., Ltd. Epoxidized soybean oil: EpoCizer W-100-EL, manufactured by DIC Corporation Bisphenol A epoxy resin: Mitsubishi Chemical Corporation, jER 1001T75 PET film: Toyobo Co., Ltd., Toyobo Ester Film E-5100 PS sheet: polystyrene sheet
[0064] <Preparation of anchor coating agent> (Preparation example a1) An anchor coating agent was obtained by adjusting 130 parts of polyester resin having a Tg of 22° C. and 0.5 parts of lubricant to a solid content of 30% with a mixed solvent of MEK and ethyl acetate.
[0065] (Preparation example a2) An anchor coating agent was obtained by mixing 30 parts of polyester resin 1 having a Tg of 22° C., 0.9 parts of silica gel, and 0.5 parts of lubricant in a mixed solvent of MEK and ethyl acetate to a solid content of 30%.
[0066] (Preparation example a3) 30 parts of polyester resin 1 with a Tg of 22°C, 0.9 parts of silica gel, and 0.5 parts of lubricant were adjusted to a solid content of 30% in a mixed solvent of MEK and ethyl acetate. 5 parts of a curing agent (solid content 75%) was added to 100 parts of the resulting resin solution to obtain an anchor coating agent.
[0067] (Preparation example a4) An anchor coating agent was obtained by adjusting 30 parts of polyester resin 2 having a Tg of 4° C. and 0.5 parts of lubricant with a mixed solvent of MEK and ethyl acetate to a solid content of 30%.
[0068] (Preparation example a5) 30 parts of polyester resin 1 with a Tg of 22°C and 0.5 parts of lubricant were adjusted to a solid content of 30% in a mixed solvent of MEK and ethyl acetate. 5 parts of a curing agent (solid content 75%) was added to 100 parts of the resulting resin solution to obtain an anchor coating agent.
[0069] <Preparation of heat sealant> (Preparation example b1) 26.4 parts of acrylic resin, 3.6 parts of vinyl chloride-vinyl acetate resin, and 0.3 parts of epoxidized soybean oil were adjusted with a mixed solvent of MEK and ethyl acetate to a solid content of 30% to obtain a heat sealing agent.
[0070] (Preparation example b2) 20.0 parts of acrylic resin, 4.4 parts of vinyl chloride-vinyl acetate resin, and 5.1 parts of bisphenol A type epoxy resin (solid content 75%) were adjusted with a mixed solvent of MEK and ethyl acetate to a solid content of 30% to obtain a heat sealant.
[0071] Example 1 <Creating a laminate> The anchor coating agent obtained in Preparation Example a1 was applied to a PET film with a bar coater at a coating rate of 3 g / m 2 After coating with and drying with a dryer, a precursor of a laminate having an anchor coat layer formed thereon (for example, 5 in FIG. 2) was obtained. Next, the heat sealant obtained in Preparation Example b1 was applied to the surface of the precursor of the obtained laminate on the side of the anchor coat layer with a bar coater in an amount of 2 g / m. 2 After drying with a dryer, the coating was dried at 80°C for 30 seconds. A laminate having a layer structure of [PET film / anchor coat layer / heat seal layer] was obtained (for example, 10 in FIG. 1).
[0072] [evaluation] The produced laminates were evaluated as follows.
[0073] <Seal strength> A 15 mm wide sample was cut out from the laminate obtained in Example 1 and heat sealed to a PS sheet at 0.2 MPa / 1 second at temperatures of 120, 150, 180, 200, and 220°C to prepare a specimen for evaluation of seal strength. The specimen obtained was subjected to heat seal strength measurement at 200 mm / min using a tensile tester (Shimadzu Corporation, small tabletop tester EZTest EZ-S). As a result, a heat seal strength of about 10.0 N to about 12.0 N was obtained at 150°C or higher. The results are shown in Table 1 and FIG. 4.
[0074] <Blocking property - heat seal layer> The surface of the prepared laminate (e.g., 10 in Fig. 1) on which the heat seal layer was formed was overlapped with one surface of a base film (a PET film with an uncoated anchor coat layer and heat seal layer) under the following conditions 1 and 2 for 24 hours, and then peeled off by hand. The state of blocking when peeled off was evaluated based on the feel when peeled off by hand. Each test was performed three times, and a three-level evaluation was performed based on the following evaluation criteria. Condition 1: 40°C atmosphere, 0.5 MPa (5.0 kgf / cm 2 ) pressure, and Condition 2: 50°C atmosphere, 0.5MPa (5.0kgf / cm 2 ) pressure [Evaluation Criteria] ◎: No blocking at all under condition 2. ○: There is some blocking under conditions 1 and 2. △: Some blocking was observed under condition 1, and some substrate damage was observed under condition 2. ×: Strong blocking occurred under condition 1, and partial destruction of the substrate was observed.
[0075] Example 2 A laminate having a layer structure of [PET film / anchor coating layer / heat seal layer] was obtained in the same manner as in Example 1, except that the anchor coating agent obtained in Preparation Example a2 was used. The heat seal strength and blocking property were evaluated in the same manner as in Example 1, and the results are shown in Table 1.
[0076] Example 3 A laminate having a layer structure of [PET film / anchor coat layer / heat seal layer] was obtained in the same manner as in Example 1, except that the heat seal agent obtained in Preparation Example b2 was used. The heat seal strength and blocking property were evaluated in the same manner as in Example 1, and the results are shown in Table 1.
[0077] Example 4 The anchor coating agent obtained in Preparation Example a3 was applied to the PET film with a bar coater at a coating rate of 3 g / m 2After coating with the above solution, the solution was dried with a dryer to obtain a precursor of a laminate having an anchor coat layer formed thereon. Next, the heat sealant obtained in Preparation Example b1 was applied to the surface of the precursor of the obtained laminate on the side of the anchor coat layer with a bar coater in an amount of 2 g / m. 2 The coating was performed at 80° C. for 30 seconds after drying with a dryer. A laminate having a layer structure of [PET film / anchor coat layer / heat seal layer] was obtained. The heat seal strength and blocking property were evaluated in the same manner as in Example 1, and the results are shown in Table 1.
[0078] Example 5 The anchor coating agent obtained in Preparation Example a2 was applied to the PET film with a bar coater at a coating rate of 4 g / m 2 After coating with the above solution, the solution was dried with a dryer to obtain a precursor of a laminate having an anchor coat layer formed thereon. Next, the heat sealant obtained in Preparation Example b1 was applied to the surface of the precursor of the obtained laminate on the side of the anchor coat layer with a bar coater in an amount of 2 g / m. 2 The coating was performed at 80° C. for 30 seconds after drying with a dryer. A laminate having a layer structure of [PET film / anchor coat layer / heat seal layer] was obtained. The heat seal strength and blocking property were evaluated in the same manner as in Example 1, and the results are shown in Table 1.
[0079] Example 6 A laminate having a layer structure of [PET film / anchor coat layer / heat seal layer] was obtained in the same manner as in Example 1, except that the anchor coat agent obtained in Preparation Example a4 (using polyester resin 2 with Tg=4°C) was used. The heat seal strength and blocking property were evaluated in the same manner as in Example 1, and the results are shown in Table 1.
[0080] Comparative Example 1 The anchor coating agent obtained in Preparation Example a5 was applied to the PET film with a bar coater at a coating rate of 1 g / m 2After coating with the above solution, the solution was dried with a dryer to obtain a precursor of a laminate having an anchor coat layer formed thereon. Next, the heat sealant obtained in Preparation Example 4 was applied to the anchor coat layer side of the obtained precursor of the laminate using a bar coater in an amount of 4 g / m. 2 After drying with a dryer, the coating was dried at 80°C for 30 seconds, and then aged at 40°C for 3 days. A laminate having a layer structure of [PET film / anchor coat layer / heat seal layer] was obtained. The heat seal strength and blocking property were evaluated in the same manner as in Example 1, and the results are shown in Table 1.
[0081] [Table 1]
[0082] (Consideration) In the results in Table 1, in Example 4, the anchor coat layer / heat seal layer=3 [g / m 2 ] / 2[g / m 2 ] and the other examples, the difference in heat seal strength from Comparative Example 1 was small. In this regard, Example 4 and Comparative Example 1 have in common that the anchor coat layer is cured with a curing agent. This makes it clear that curing of the anchor coat layer has a strong effect of reducing the heat seal strength, especially in the low temperature range of 180°C or less. The effect of the present invention is that, despite the heat sealing at a low temperature of 150°C, a heat seal strength that fully meets the required performance can be obtained. The reason for this is the change in concept of endowing the anchor coating agent, which has been thought of as a role to assist the adhesion between the base film and the heat seal agent, with the same heat sealability as the heat seal agent. In other words, the adhesiveness was improved by increasing the coating amount of the anchor coating agent, which was generally applied in a thin film. Furthermore, by not curing the anchor coating layer, the resin component in the anchor coating layer softens and melts even at low temperatures, allowing the adhesive function to be expressed. [Explanation of symbols]
[0083] 1. Base film 2 Anchor coat layer 3 Heat seal layer 5. Precursor sheet of laminate 10 Laminate 20 Lid material 30 containers 40 Contained object (contents) 100 packages
Claims
1. The film has a base film, an anchor coat layer provided on one surface of the base film, and a heat seal layer provided on the anchor coat layer, The anchor coat layer has a coating amount of 1 g / m after drying. 2 Super 6g / m 2 Is less than or equal to A laminate comprising:
2. The laminate according to claim 1 , wherein the anchor coat layer contains a polyester resin.
3. 3. The laminate of claim 1 or 2, wherein the anchor coat layer is not isocyanate cured.
4. The laminate according to claim 1 or 2, wherein the anchor coat layer does not contain an acrylic resin.
5. 3. The laminate according to claim 1, wherein the heat seal layer contains at least an acrylic resin and / or a vinyl chloride-vinyl acetate copolymer resin.
6. The laminate according to claim 5 , wherein the heat seal layer further contains an epoxy resin.
7. The heat seal layer has a coating amount of 1 g / m after drying. 2 6g / m or more 2 The laminate according to claim 1 or 2, wherein:
8. The ratio of the coating weight of the anchor coat layer to the dry coating weight of the heat seal layer is 3. The laminate according to claim 1, wherein the coating weight of the anchor coat layer / the coating weight of the heat seal layer is 0.1 or more.
9. 3. The laminate according to claim 1, wherein the substrate film is a film having a surface in contact with the anchor coat layer, the surface being constituted by a polyester layer.
10. The laminate according to claim 1 or 2, which is used as a lid material.
11. A container having a recess and the laminate according to claim 10 as a lid material, The packaging body, wherein the lid material is heat-sealable to the opening of the container.
Citation Information
Patent Citations
Ground detecting circuit
JP1980080067A